Tracing Toni Morrison’s Narrative Strategies in Sula: The Afterlife of Slavery in Black Narrative Form - Tatit Hariyanti; Dewi, Septi Riana (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
This paper examines Toni Morrison’s narrative strategies in her novel Sula, focusing on how she reconstructs and transmits the complex history of Black people to younger generations. Morrison’s literary works serve as a vehicle for preserving the legacy of Black history, often obscured or distorted. Employing both objective and expressive methodologies, this study analyzes the novel alongside relevant critical sources that explore Morrison’s narrative techniques and thematic intentions. The findings reveal that Morrison consistently employs distinctive narrative strategies in Sula, including a non-linear plot structure that juxtaposes past, present, and future; character development rooted in fragments of memory and historical detail; and the deliberate use of historical, geographical, and cultural settings. Moreover, Morrison integrates the Black community not only as a backdrop but as a vital thematic element and a collective character within the novel. This study underscores Morrison’s commitment to centering Black experiences and histories through innovative narrative forms.